On emergent particles and stable neutral plasma balls in SU(2) Yang-Mills thermodynamics - Hofmann, Ralf; Grandou, Thierry (Universe, 2022)
For a pure SU(2) Yang-Mills theory in 4D, we revisit the spatial (3D), ball-like region of radius r0 in its bulk subject to the pressureless, deconfining phase at T0=1.32Tc, where Tc denotes the critical temperature for the onset of the deconfining-preconfining phase transition. Such a region possesses finite energy density and represents the self-intersection of a figure-eight shaped center-vortex loop if a BPS monopole of core radius ∼r052.4, isolated from its antimonopole by repulsion externally invoked through a transient shift of (anti)caloron holonomy (pair creation), is trapped therein. The entire soliton (vortex line plus region of self-intersection of mass m0 containing the monopole) can be considered an excitation of the pressureless and energyless ground state of the confining phase. Correcting an earlier estimate of r0, we show that the vortex-loop self-intersection region associates to the central part of a(n) (anti)caloron and that this region carries one unit of electric U(1) charge via the (electric-magnetic dually interpreted) charge of the monopole. The monopole core quantum vibrates at a thermodynamically determined frequency ω0 and is unresolved. For a deconfining-phase plasma oscillation about the zero-pressure background at T=T0, we compute the lowest frequency Ω0 within a neutral and homogeneous spatial ball (no trapped monopole) in dependence of its radius R0. For R0=r0 a comparison of Ω0 with ω0 reveals that the neutral plasma oscillates much slower than the same plasma driven by the oscillation of a monopole core.